EVALUASI TINGKAT KERUSAKAN JALAN SEBAGAI DASAR PENENTUAN PERBAIKAN JALAN PADA RUAS JALAN SOEKARNO HATTA KOTA KASONGAN (Evaluation Of Road Damage As A Basis For Determining Road Improvements On Soekarno Hatta Road, Kasongan City) - Aria Hansen; Ibot Satriady (Huma Tabalien Jurnal (HTJ) Teknik Sipil, 2023)
This study aims to identify road pavement damage. Identification of road damage includes the type of damage and the level of road damage so that the road pavement condition value and alternatives for handling the road damage can be identified. The research location was carried out on the Seokarno Hatta road section, Kasongan city Keywords: Implementation Methods / Terms of Reference, Resources